Tax Avoidance Pasca Pandemi Covid 19: Studi Pada Perusahaan Farmasi Yang Terdaftar di BEI - Juliati (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
This research is to determine the level of tax avoidance after the Covid-19 pandemic because the government has prepared various kinds of fiscal rules for taxpayers to pay taxes according to applicable regulations. Design/methodology/approach: The research methods used are descriptive and quantitative. The variable used was tax avoidance measured using ETR and CETR. The test was conducted using different levels of tax avoidance before and after covid 19. The expected research result is that the level of tax avoidance is getting smaller because the government has provided a lot of regulatory leeway during the Covid-19 pandemic. Therefore, after the Covid-19 pandemic, taxpayers are expected to increase ETR and CurrentETR.